The Implications of the Local Context in Global Online Education - Rye, Ståle Angen; Støkken, Anne Marie (International Review of Research in Open and Distributed Learning, 2012)
This paper investigates how features in students’ everyday life influence their participation in online global collaboration, and it suggests that students’ local context should be recognised as a significant part of their educational space. In this exploratory case study of students engaged in a global online master’s programme, the discussion is organised under three main headings: the social, material, and cultural dimensions of students’ daily life. The paper shows how the influence of the students’ local context typically creates a situation whereby the online learning space is characterised by inequality. This recognition should be taken into account when providers of online education design courses and make provision for student support. In this way, the inequalities can be seen as a resource for learning rather than as a problem.